Performance of volatility asset as hedge for investor's portfolio against stress events: COVID-19 and the 2008 financial crisis. Issue 3 (September 2022) - Chendurpandian, Chinnaraja; Pandey, Piyush
Abstract: Under stress events, most of the asset prices tend to be positively correlated, breaking the diversification benefits. In this study, we explore the performance of different assets particularly during stress events (the 2008 crisis and the COVID-19 crisis) which can come to the rescue of portfolio managers as hedging strategies. Further, the analysis evaluates the performance of different combinations of portfolios with and without including volatility assets. Empirical results indicate that with only an allocation of 5% of the portfolio to volatility asset class, investors with different risk appetites were able to achieve 10% expected returns with reduced uncertainty.